&Lt;i>Escherichia Coli</I&gt; - Recent Advances on Physiology, Pathogenesis and Biotechnological Applications 2017
DOI: 10.5772/67776
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils: The Ultimate Solution to Antimicrobial Resistance in <i>Escherichia coli</i>?

Abstract: Antimicrobial resistance (AMR) is on the rise; the only solution for overcoming this is through accelerated drug discovery. At current, bacterial evolutionary rates is still clearly the undisputed winner in this war. To circumvent this, evolution of resistance need to be curbed and this can only be effective via novel approaches, one of which includes the use of a resistance modifying agent. The criterion to qualify as a resistance modifier necessitates the co-administration of the agent with an inhibitor that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 64 publications
3
15
0
Order By: Relevance
“…Nonetheless, owing to its nature of being one of the major constituents in many EOs, we postulated that BCP might involve altering of the permeability of the bacterial membrane. Previously, several studies have reported the involvement of EOs in the altering the bacterial membrane permeability and intracellular leakage (Trombetta et al 2005;Yap et al 2013;Yang et al 2017;Yang et al 2019). Hence, as a proof of concept, the measurement of zeta potential and UV-absorbing materials as well as the efflux pump assays were carried out on B. cereus treated with BCP to evaluate the mode of action of BCP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, owing to its nature of being one of the major constituents in many EOs, we postulated that BCP might involve altering of the permeability of the bacterial membrane. Previously, several studies have reported the involvement of EOs in the altering the bacterial membrane permeability and intracellular leakage (Trombetta et al 2005;Yap et al 2013;Yang et al 2017;Yang et al 2019). Hence, as a proof of concept, the measurement of zeta potential and UV-absorbing materials as well as the efflux pump assays were carried out on B. cereus treated with BCP to evaluate the mode of action of BCP.…”
Section: Discussionmentioning
confidence: 99%
“…The zeta potential value provides information about the membrane potential, which can be related to the metabolic state of bacteria whereby at higher growth rates, zeta potential values are more negative (Yang et al 2018). The alteration in the zeta potential value, becoming less negative, together with the increased surface permeability eventually leads to decreased cell viability (Yang et al 2017). Under normal physiological conditions, the net negative bacterial surface charge is balanced by positively charged counter ions in the surrounding media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has triggered the demand for continuous discovery and commercialization of applications for novel, yet effective new antimicrobial agents. However, the limiting factor that remains is the rate of new drug development versus the rate of bacterial evolution, with bacterial evolution emerging as the undisputed winner [ 2 ]. Several strategies have been proposed to tackle this issue, including newer drug rotation and combination therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, essential oils are also known for their antibacterial, antifungal and antiviral properties [56][57][58]. Generally, essential oils consist of 20 to 60 components which are highly volatile but none of which are actually lipid in nature; they are thus not considered true oils.…”
Section: Essential Oilsmentioning
confidence: 99%